Political Structure of Eastern Rumelia Autonomy Region (1879-1885) - Vinarov, Ivan (Research Papers, 2019)
During the first years of its existence the Bulgarian statehood is built in two centers. The current research aims is to clarify the political structure of the “second Bulgaria”, called Eastern Rumelia. The research is based on historic and legal analysis. The main conclusion is that Autonomous Region is a purely Bulgarian province, bearing the characteristics of a Bulgarian national state. Its population does not bear in its heart the dream of a brilliant autonomy, but for joining the Principality of Bulgaria.